Pediatric Dialysis - Warady, Bradley A.; Schaefer, Franz; Alexander, Steven R. (Springer US : Imprint: Springer, 2012)
Since the inaugural publication of Pediatric Dialysis in 2004, a wide range of advances have taken place in dialysis-related care, leading to a wealth of new knowledge in the field.  Pediatric Dialysis, Second Edition brings this knowledge together to provide the most comprehensive source of state-of-the-art information on the dialysis of infants, children and adolescents.  With new chapters, updated chapters and references, and contemporary, unique perspectives from authors who are leaders in the global pediatric nephrology community, Pediatric Dialysis, Second Edition is, once again, an authoritative reference that will facilitate best practices in both acute and chronic dialysis.  Experienced clinicians and trainees alike will find Pediatric Dialysis, Second Edition not only another valuable contribution to the literature but an indispensable guide to managing their pediatric patients on dialysis.